2019
DOI: 10.1002/brb3.1465
|View full text |Cite
|
Sign up to set email alerts
|

PACAP27 mitigates an age‐dependent hippocampal vulnerability to PGJ2‐induced spatial learning deficits and neuroinflammation in mice

Abstract: BackgroundInflammation in the brain is mediated by the cyclooxygenase pathway, which leads to the production of prostaglandins. Prostaglandin (PG) D2, the most abundant PG in the brain, increases under pathological conditions and is spontaneously metabolized to PGJ2. PGJ2 is highly neurotoxic, with the potential to transition neuroinflammation into a chronic state and contribute to neurodegeneration as seen in many neurological diseases. Conversely, PACAP27 is a lipophilic peptide that raises intracellular cAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 117 publications
0
12
0
Order By: Relevance
“…52 There are 3 fluoro-jade dyes-Fluoro-Jade, Fluoro-Jade B, and Fluoro-Jade C. 53 Fluoro-Jade B, and Fluoro-Jade Care extensively used for identifying and quantifying degenerated neurons in neurotrauma studies. [54][55][56][57][58][59] In this study, we used Fluoro-Jade B to stain and quantify the degenerating neurons in the stab wound injury. Results showed large number of degenerating neurons around the injury site in injured + treated with PBS (I + PBS1 and I + PBS2 groups) and injured + IFNγ or IL-1β treated groups (I + IFN-γ and I + IL-1β) a day after injury, with a significant difference between PBS-treated and IFN-γ-or IL-1β-treated groups.…”
Section: Il-1β Are Able To Increase Secretion Of Bdnf Through Astrocymentioning
confidence: 99%
“…52 There are 3 fluoro-jade dyes-Fluoro-Jade, Fluoro-Jade B, and Fluoro-Jade C. 53 Fluoro-Jade B, and Fluoro-Jade Care extensively used for identifying and quantifying degenerated neurons in neurotrauma studies. [54][55][56][57][58][59] In this study, we used Fluoro-Jade B to stain and quantify the degenerating neurons in the stab wound injury. Results showed large number of degenerating neurons around the injury site in injured + treated with PBS (I + PBS1 and I + PBS2 groups) and injured + IFNγ or IL-1β treated groups (I + IFN-γ and I + IL-1β) a day after injury, with a significant difference between PBS-treated and IFN-γ-or IL-1β-treated groups.…”
Section: Il-1β Are Able To Increase Secretion Of Bdnf Through Astrocymentioning
confidence: 99%
“…It has been demonstrated that the Nrf2/HO-1 pathway protects the brain from ischemic injury by attenuating oxidative damage (Ge, Shao, & Zhu, 2018;Xu et al, 2015). Neuroinflammation is implicated in the development and progression of neurological diseases, and contributes to the exacerbation and propagation of CNS injury (Avila et al, 2019). The nuclear factor-kappa B (NF-κB) signaling pathway is pivotal in mediating neuroinflammation which is activated by proinflammatory cytokines (Chung et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was revealed that fatty acid metabolism could affect the production of inflammatory substances. PGJ2 is reportedly involved in the pathological changes observed in Alzheimer’s disease and Parkinson’s disease, as well as mediating oxidative stress in neuronal apoptosis and the accumulation/aggregation of ubiquitinated proteins [ 27 , 47 ]. Leukotrienes are potent pro-inflammatory mediators that are synthesized from arachidonic acid.…”
Section: Discussionmentioning
confidence: 99%